Analysis of the quiet life hypothesis implications in the WAEMU banking sector - EGGOH, COMLANVI JUDE; DANNON, Hodonou; Ndiaye, Abdoulaye (My University, 2021)
This paper investigates the relationship between market power and cost efficiency for a sample of 63 banks in the West African Economic and Monetary Union (WAEMU) from seven countries over the period of 2004–2016. Our empirical methodology relies on a panel data analysis. Our results show that an increase in market power reduces banking efficiency in the WAEMU countries, and therefore suggest that competition in the banking sector improves cost efficiency. These findings are consistent with the quiet life hypothesis. However, our nonlinear investigation indicates that beyond a specific threshold of competition, this latter deteriorates the cost efficiency of banks, thus confirming the efficient structure hypothesis. These results indicate the efficiency improvement of the banking system in the WAEMU countries by the control of operating costs. Moreover, the central bank and the banking regulators must increase their supervision over the most competitive banks of the WAEMU.
Keywords: Banking competition; Market power; Cost efficiency; WAEMU